Soft tissue balance using the tibia first gap technique with navigation system in cruciate-retaining total knee arthroplasty - Matsumoto, Tomoyuki (Springer-Verlag, 2011)
PURPOSE: The procedures of bone cut and soft tissue balancing in total knee arthroplasty (TKA) are usually performed using the measured resection technique or the gap technique; however, the superiority of these techniques is controversial. An increase of extension gap after resection of the femoral posterior condyle and a difference between gaps before and after femoral component placement have been reported. We therefore postulated that the use of the tibia first gap technique might have an advantage in avoiding the mismatch before and after resection of the femoral posterior condyle and femoral component placement. METHODS: We performed cruciate-retaining TKAs for 60 varus type osteoarthritic patients with tibia first gap technique using a CT-free navigation system. A TKA tensor designed to facilitate soft tissue balance measurements throughout the range of motion with a reduced and repaired patello-femoral joint was used to assess soft tissue balance (joint gap and varus ligament balance) at extension and flexion between the basic value after tibial cut and the final value following femoral cut and with the femoral component in place. RESULTS: Whereas varus ligament balance at flexion showed significant decrease in the final value at flexion due to the amount of femoral rotation, the basic value of the joint gap before femoral osteotomy reflected the final value following femoral cut and with the femoral component in place. CONCLUSION: The tibia first gap technique may have the advantage that surgeons can predict final soft tissue balance before femoral osteotomies.